Kenyan Sign Language Acquisition Assessment Tool - and Tools Competition (2025)
Our tool, to our knowledge, is the first AI-enhanced sign language acquisition assessment in Africa, designed to support early-grade deaf and hard of hearing learners in mastering their first language, sign language. It measures both expressive and receptive KSL skills using video-based prompts and interprets responses through AI, providing rapid, accessible feedback. By generating disaggregated, […]